Penguatan Kesetiakawanan Sosial Peserta Didik melalui Nilai Budaya Perayaan Maudu Lompoa - Hendra Hendra; Budijanto Budijanto; I Nyoman Ruja (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The purpose of this study is to determine the strengthening of social solidarity of learners through the cultural values of celebration maudu lompoa. The research was conducted by qualitative descriptive method. The results revealed that the culture of maudu lompoa celebration contains six aspects, namely as follows (1) as the basis for building togetherness of family feeling, (2) as the basis for building mutual help with mutual cooperation, (3) as a basis to build mutual understanding of the condition of the desire to share, (4) as a basis to build attitude feel the same from the taste solidarity, (5) as the basis for building the sensitivity to others of compassion, and (6) as a basis for building an attitude of perseverance from the work ethic. Cultural celebration maudu lompoa very appropriate as a source of learning in strengthening social solidarity learners.Abstrak: Tujuan penelitian ini adalah untuk mengetahui penguatan kesetiakawanan sosial peserta didik melalui nilai budaya perayaan maudu lompoa. Penelitian dilakukan dengan metode kualitatif deskriptif. Hasil penelitian mengungkapkan bahwa budaya perayaan maudu lompoa mengandung enam aspek, yaitu (1) sebagai dasar membangun kebersamaan dari rasa kekeluargaan, (2) sebagai dasar membangun sikap saling membantu dengan gotong royong, (3) sebagai dasar membangun sikap saling mengerti keadaan dari keinginan untuk berbagi, (4) sebagai dasar membangun sikap merasakan hal yang sama dari rasa solidaritas, (5) sebagai dasar membangun sikap kepekaan kepada orang lain dari rasa cinta kasih, dan (6) sebagai dasar membangun sikap ketekunan dari etos kerja. Budaya perayaan maudu lompoa sangat tepat dijadikan sebagai sumber pembelajaran dalam menguatkan kesetiakawanan sosial peserta didik.